Application of phase change materials in 4D printing: A review. (2021) - Mehta, Parth; Sahlot, Pankaj
Abstract: Evolution in additive manufacturing is rapid nowadays and it has discovered 4th dimension in myriad of engineering applications. 3D printing technology has gained attention in recent years when Skylar Tibbits has introduced 4th dimension i.e. time in it. Phase change materials can transform its shape, size or properties as a response to external stimuli like change in temperatures, PH values, UV radiation, electric field, etc. 3D Printing with the help of phase change materials creates better opportunities within the conditions where human access is sort of impossible. The recent progresses of 4D printing with the help of phase change materials is presented in this review. Various applications of 4D printing technology are covered which has the major role in pharmaceutical industry, biomedicine industry, and soft robotics. This review will provide useful insight for future progresses on applications of phase change materials in 4D printing.